PENALARAN DALAM ESAI MAHASISWA UNIPA SURABAYA - Indrayanti, Tri; Eko Retnosari, Ira (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2017)
This article aims at describing reasoning essay in paragraph of the students of PGSD2015 Unipa Surabaya. The approach used in this article is descriptive qualitative in which the data collection used library and documentation methods. The data collection procedures in this research are (1) essay collection, (2) codification of students’ names, (3) categorization of the students’ data using reasoning paragraph, (4) data management, (5) calculation of the result percentage. The data analysis of this research uses qualitative descriptive. It means that it only describes the reasoning paragraph. The stages used in this analysis are (1) data collection, (2) data classification, and (3) interpretation. The validity of this research usesobservation perseverance technique, triangulation, and peer review. The result of this analysis is found the use of deductive and inductive reasoning. In using both reasonings, the students of PGSD 2015 are good.